Phytoremediation of Lead (Pb) Particulate as a Nature-Based Solution for a Healthier Environment - Pambudi, Priyaji Agung; Handoko, Roni Setyo (Universitas Pattimura, 2025)
Lead (Pb) particulates are a serious environmental issue due to their impact on health and ecosystems. These pollutants stem from emissions of vehicles, industries, and mining. This study aims to explore the potential of plants as phytoremediators of Pb used a literature review with data triangulation from scientific journals and institutional reports. Content analysis, tabulation, and exploratory descriptive analysis were conducted. Lead, with an atomic number of 82 and an atomic weight of 207.20, is a hazardous metal that can cause kidney damage, hypertension, anemia, nerve damage, reduced fertility, miscarriages, and lower IQ. Pb particulates can adhere or fall on leaf surfaces and are absorbed through stomata. This process occurs because the size of Pb particulates (0.2-4 µm) allows them to be absorbed through stomatal openings (2-10 µm) when they open to take in CO2, thus allowing Pb to enter and accumulate in plant tissues. Through this physiological mechanism, plants can be used as effective solutions for absorbing Pb. Some plants with high effectiveness include Polyaltia longifolia, Swietenia macrophylla, and Bougainvillea spectabilis. Planting these species in industrial zones and roads can improve air quality and provide ecosystem benefits, such as clean air, habitat space, thermal comfort, and aesthetic value.